On Dividend Restrictions and the Collapse of the Interbank Market - Tsomocos, D; Goodhart, C; Peiris, U; Vardoulakis, A (2010)
Until recently, financial services regulation remained largely segmented along national lines. The integration of financial markets, however, calls for a systematic and coherent approach to regulation. This paper studies the effect of market based regulation on the proper functioning of the interbank market. Specifically, we argue that restrictions on the payout of dividends by banks can reduce their expected default on (interbank) loans, stimulate trade in this market and improve the welfare of consumers.